The Analysis of Fish and Other Animal Food Self-Sufficiency in 26 Districts/Citiesof West Java 2012 - Yayuk Farida Baliwati; Iqbal Mahendra Saputra (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2014)
This study was aimed to determine the actual situation of production and consumption, and animal food adequacy ratio based on net production devided to normative consumption. This study used cross sectional study and conducted at 26 districts/cities in West Java Province. The collecting, processing, and analyzing of data since January until July 2014. This study used secondary data that had become a constant number. The results of this study showed that 21 (80,8%) districts/cities have actual comsumption below the normative consumption. Fishes consumption and the others animal consumption in West Java citizen in 2012 were included to low category. Fishes contibute in animal food consumption about 13-44% so that became the one of the determining commodity for animal food pattern in 26 districts/cities in West Java Province. Fishes commodity also became animal food production pattern almost in those all districts/cities in West Java Province except Sukabumi District, Bandung City, Depok City, and Cimahi City. The pattern of citizen’s food consumption has been utilized the potential yet, so was not always approrite with the pattern of district food production. In 2012, there were 13 (50%) districts/cities in West Java Province that have became self-sufficiency in fishes and the others animal food.Keywords: Fish and the other animal food, food self-sufficiency, consumption and production.